Shriver & atkins' Inorganic chemistry - Atkins, Peter (Oxford : Oxford University Press, 2010)
Key Features The author team brings together chemical educators and researchers who are at the forefront of their fields to produce a text which combines authoritative coverage with a clear and lucid writing style Basic chemical principles are set out clearly in Foundations and are fully developed throughout the text, culminating in the cutting-edge research topics of the Frontiers A completely repackaged Part 2 divides the descriptive chemistry into Essentials and Details, making it easier for the reader to draw out the key principles, before exploring the reactions exemplifying these principles in more depth An increased number of worked examples, problems, and exercises, further aid students understanding Contextual examples illustrating the impact of inorganic chemistry on everyday life, and a refreshed full-colour text design, increase the students interest in and engagement with the text to make their learning more effective The Online Resource Centre offers additional resources for both lecturers and students, enhancing the value of the text as a teaching and learning tool New to this edition The introduction of a new chapter on periodic trends provides an accessible outline for students of the major trends exhibited by the chemical elements, before the descriptive chemistry is covered in detail throughout the rest of Part 2 Additional worked examples actively engage students and test their understanding Major revision of chapter 10, Hydrogen, to introduce technologically relevant nuclear properties, renewable hydrogen production, and complexes of transition metals with hydrido or dihydrogen ligands Increased coverage of green chemistry A new approach to presenting the descriptive chemistry chapters in Part 2 splits the content into Essentials and Details, providing students with a summary of the key reactions of each group before drilling down into more detail, resulting in a greater focus on periodicity and the highlighting of key trends Expanded use of co
Index 813-824p.; Reprint 2014.
Keywords: Coordination chemistry; Group elements; Organometallic chemistry; Oxidation